Attitudes of Young Moroccans towards the Use of Code-switching in their Facebook Interactions - Khawla Khoumssi (Journal of English Language Teaching and Linguistics, 2020)
Code-switching is part of the daily speech of a huge number of Moroccans. The insertion of French words and expressions in the Moroccan individuals’ verbal interactions gives the impression that they are modern, educated and belonging to a higher social class. This kind of language is very common among young Moroccans, and considered as a sophisticated way of communicating, especially in social networking sites, mainly Facebook. However, there is a controversy over the use of code-switching all over the world, as some consider it a sign of first language attrition and others, on the other side, perceive it as a conscious act performed by bilingual speakers to serve different communication intents. The main purpose behind this research is to holistically investigate, through survey questionnaire, the phenomenon of code-switching among young Moroccans in Facebook, since it is highly frequent among this category, trying to trace their attitudes towards this linguistic phenomenon, and whether they consider it as a communicative strategy or a sign of Moroccan language attrition. It also attempts to find out whether demographic variables such as, ‘age’, ‘level of education’ and ‘type of school’ can be considered among factors that might influence the way young Moroccan Facebook users perceive CS. Findings achieved from statistical analysis of data also showed that socio-demographic variables mainly age, level of education, type of school, are responsible for variations at the level of attitudes of young Moroccan Facebook users.